Evaluation of a probiotic mixture in the started birds feeding of heavy pure breeds B4 in a production unit - Rodríguez, Marlen; Milián, Grethel; Rondón, Ana j.; Bocourt, R.; Beruvidez, A.; Crespo, Elayne (Cuban Journal of Agricultural Science, 2016)
Email: marlen.rodriguez@umcc.cuIn order to evaluate the effect of the inclusion of a probioticmixture (bio-preparation) based on Lactobacillus salivariusC65 andBacillus subtilis E44 strains on the diet of started birds of heavy purebreeds, a research was conducted at the Unidad Genética Avícola“Granma” from Pedro Betancourt municipality, Matanzas. Thestudy was carried out in a period of 35 days, between December2013and January 2014.The design was completely randomized andtwo treatments were evaluated: T1) basal diet (control) and T2) basal diet plus bio-preparations mixture, in ratio 1:1. A total of 600 heavy pure breeds B4 birds were used, (300 per treatment) with an average weight of 42 grams at birth. They stayed on floor under similar management and feeding conditions. The liveweight, intake, conversion in weight per kilogram of intake food, mortality and birds viability was determined. The animals that received the probiotic mixture had a high liveweight during the rearing, exceptin the first two weeks, in which there were not differences between treatments. There were differences (P<0. 05) in the conversion per bird and the mortality percentage and viability, in favor of the treatment with the probiotic mixture. It concludes that it is possible to use this bio -preparation in the started birds feeding of heavy pure breeds, since the best biometric results were found in the group of birds treated with the animal additive.Key words: probiotic mixture, heavy pure breeds